Playing by ear - Harse, Deborah; Harse, Deborah (Academic Video Online, 2014)
Playing By Ear is a short documentary about the Institution For The Blind in Delhi, India and the blind boys there who surmount obstacles to pursue their dreams. They focus on academics and also study music and participate in sports. Cricket is especially popular, and they play the game with a ball containing beads to make a sound so that they can hear the ball as it approaches them. They are well cared for by a supportive staff, receive a good education and some go on to college. This short film is an uplifting success story with a positive message for all of us.